2015
DOI: 10.1128/jb.00389-15
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Antibiotic Tolerance in Sod-Deficient Mutants Is Dependent on the Energy Source and Arginine Catabolism in Enterococci

Abstract: Enterococci are naturally tolerant to typically bactericidal cell wall-active antibiotics, meaning that their growth is inhibited but they are not killed even when exposed to a high concentration of the drug. The molecular reasons for this extraordinary tolerance are still incompletely understood. Previous work showed that resistance to killing collapsed specifically in mutants affected in superoxide dismutase (Sod) activity, arguing that bactericidal antibiotic treatment led to induction of a superoxide burst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…These results thus further support the important contribution of SOD activity to antibiotic tolerance, which is growth phase specific and negligible under rapid growth conditions as the absence of SOD activity does not affect antibiotic tolerance in exponentially growing P. aeruginosa. Our results with the sodAB mutant are consistent with studies in Enterococcus faecalis (Bizzini et al, 2009;Ladjouzi et al, 2015), Campylobacter jejuni (Hwang et al, 2013), Acinetobacter baumannii (Heindorf et al, 2014), and E. coli (Dwyer et al, 2007;Wang et al, 2014), where loss of SODs also enhances bactericidal antibiotic killing. These stand in contrast to other studies performed in exponentially growing E. coli reporting that the sodA sodB mutant exhibited similar susceptibility to ampicillin, gentamicin, and norfloxacin killing to the wild-type strain (Wang and Zhao, 2009;Ezraty et al, 2013), and that overexpression of sodA or sodB did not mitigate ampicillin and ofloxacin killing (Orman and Brynildsen, 2016).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results thus further support the important contribution of SOD activity to antibiotic tolerance, which is growth phase specific and negligible under rapid growth conditions as the absence of SOD activity does not affect antibiotic tolerance in exponentially growing P. aeruginosa. Our results with the sodAB mutant are consistent with studies in Enterococcus faecalis (Bizzini et al, 2009;Ladjouzi et al, 2015), Campylobacter jejuni (Hwang et al, 2013), Acinetobacter baumannii (Heindorf et al, 2014), and E. coli (Dwyer et al, 2007;Wang et al, 2014), where loss of SODs also enhances bactericidal antibiotic killing. These stand in contrast to other studies performed in exponentially growing E. coli reporting that the sodA sodB mutant exhibited similar susceptibility to ampicillin, gentamicin, and norfloxacin killing to the wild-type strain (Wang and Zhao, 2009;Ezraty et al, 2013), and that overexpression of sodA or sodB did not mitigate ampicillin and ofloxacin killing (Orman and Brynildsen, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…While several groups have previously reported that bactericidal antibiotics induce production of reactive oxygen species, including superoxide and hydroxyl radicals, which contribute to their off-target killing mechanism ( Dwyer et al, 2007 ; Grant et al, 2012 ; Sampson et al, 2012 ; Imlay, 2013 ; Van Acker et al, 2016 ), others have refuted these observations ( Keren et al, 2013 ; Liu and Imlay, 2013 ). Superoxide stress also induces anti-oxidant defenses such as superoxide dismutases (SOD), which in turn modulate antibiotic lethality as we and others have reported ( Bizzini et al, 2009 ; Hwang et al, 2013 ; Ladjouzi et al, 2013 , 2015 ; Heindorf et al, 2014 ; Wang et al, 2014 ; Martins et al, 2018 ). We recently demonstrated that induction of SOD activity confers multidrug tolerance to stationary phase P. aeruginosa through alteration of the cell envelope permeability and increased drug accumulation ( Martins et al, 2018 ).…”
Section: Introductionmentioning
confidence: 96%
“…ATP can be generated when carbamoyl phosphate is dephosphorylated by carbamate kinase (31,32). This pathway is known to be particularly active in response to environmental stress (33,34) and is of special interest since poly(P) accumulation is associated with bacterial stress resistance. The levels of arginine, citrulline, and ornithine were higher in the ppk2::Tn and ppx1::Tn mutants than in the wild type (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This can be reversed by overexpression in the mutant of KatA, the dominant P. aeruginosa catalase 4 , or by restoration of Sod activity 22 . Many other bacteria become more susceptible to antibiotics on Sod deletion, including Enterococcus faecalis 9,23,24 , Campylobacter jejuni 8 , Acinetobacter baumanii 7 , Staphylococcus aureus 24 and E. coli in stationary-phase 25 but maybe not in exponentially growing cultures 15 . Deletion of the catalase-peroxidase katG or the alkyl hydroperoxide reductase ahpC also potentiates some antibiotics in E. coli 15 .…”
Section: Introductionmentioning
confidence: 99%